Disability in Islamic Law : historical applications and today’s challenges - Wentz, Agata (Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2018)
The author of the article conducts an analysis of Islamic law’s perspective on disability by examining disability-related terminology and some texts from the primary legal sources of Islam – the Qur’an and the Sunnah. After a brief overview of the Muslim faith and the nature of Islamic jurisprudence, the chapter proceeds with a description of the nomenclature related to disability followed by a brief overview of historical perceptions. The paper concludes with insights into the condition of autistic children in the United Arab Emirates today
Keywords: disability; islam; Sharia; Quran; sunnah; Islamic law